ANALYSIS OF FACTORS AFFECTING BEEF SUPPLY IN THE DISTRICT DELI SERDANG - G M T Siahaan; Hasnudi; E Mirwandhono; M Tafsin; N Ginting (Talenta Publisher, 2018)
One reason for the low number of beef consumption in Indonesia in particular Deli Serdang is the least amount of beef offered traders. Therefore, a study was conducted in March 2016 to April 2016 to examine the factors that influence the beef supply in Deli Serdang. The method used was survey with interviews to traders guided by questionnaire. The sample selection started on the personal judgment of researchers who claimed that the selected sample truly represented. Methods of data collection were to collect primary and secondary data. The results showed that marketing cost factors and profit affected the amount of beef offered. The purchase price was not influenced of a great day and the influence of other commodities not affect partially on the amount of beef offered.